DIGITALIZATION OF ACCOUNTING INFORMATION IMPACT ON MSMEs' PROFITABILITY AND PRODUCTIVITY - mutoharoh; Winarsih; zahrah Buyong, Siti (Universitas Airlangga, 2020)
This study aims to examine the impact of digitalization of accounting information on MSMEs profitability and productivity. The population in this study wasMSMEs in Semarang which were registered at the Cooperative and UMKM Agency of Semarang as of October 2019 totaling 17.010 units. There are 300 cases selected using purposive sampling method with the criteria that the companies use computerize transaction recording and/or utilize smart devices for business communication. The primary data were collected from MSMEs' manager through questionnaire that wasdistributed in several public events such as exhibition and seminars. The study took the simple regression analysis utilizing SPSS 22.0 software. The findings show that that digitalization of accounting information has significant impacts on increasing profitability. Another finding shows that digitalization of accounting information does not affect the companies' productivity. This research is based on the Technological Acceptance Model (TAM) theory and the Schumpeterian theory. In practice, the results of this study can be socialized to the MSMEsmanagers so that theycan use this to evaluate the implementation of accounting information in their business. This study can also be used by government and others related parties to consider in providing business assistance for MSMEs to improve the impact of digitalization ofaccounting information